Ectoparasites and other ectosymbiotic arthropods of vertebrates in the Great Smoky Mountains National Park, USA - Reeves, Will K.; Durden, Lance A.; Ritzi, Christopher M.; Beckham, Katy R.; Super, Paul E.; Oconnor, Barry M. (Zootaxa, 2007)
We review previously published accounts of ectoparasites and other ectosymbiotic arthropods of vertebrates and report on the collections from 4 species of reptiles, 54 species of birds, and 47 species of mammals from the Great Smoky Mountains National Park, or immediately adjacent lands in North Carolina and Tennessee, USA.  Our list includes 1 species of beetle, 2 hemipteran bugs, 9 flies, at least 42 species of lice, 23 species of fleas, and at least 75 species of Acari (11 ticks/64 mites).  We discuss the potential for transmission of pathogens by these ectoparasites and the relevance of disjunct populations of boreal species at high elevations in the Great Smoky Mountains.